Mixture of Synthetic Plant Volatiles Attracts More Stick Tea Thrips Dendrothrips minowai Priesner (Thysanoptera: Thripidae) and the Application as an Attractant in Tea Plantations - Zhengwei Xu; Guowei Zhang; Yan Qiu; Zongxiu Luo; Xiaoming Cai; Zhaoqun Li; Lei Bian; Nanxia Fu; Li Zhou; Fida Hussain Magsi; Zongmao Chen; Xiaoming Zhang; et al. (Plants, 2024)
The stick tea thrip (Dendrothrips minowai) is one of the most serious sucking pests of tea plants (Camellia sinensis) in China, North Korea, and Japan. Plant volatile lures are widely used for both monitoring and mass trapping. Previously, we demonstrated that sticky traps baited with p-anisaldehyde, eugenol, farnesene, or 3-methyl butanal captured significantly more D. minowai in tea plantations, with p-anisaldehyde notably capturing the most. In this study, we showed that D. minowai adults exhibited significantly higher attraction to mixtures of p-anisaldehyde, eugenol, and farnesene compared to an equivalent dose of p-anisaldehyde alone in H-tube olfactometer assays under laboratory conditions. Moreover, in field experiments conducted in 2022, rubber septa impregnated with a ternary blend of p-anisaldehyde, eugenol, and farnesene (at 3–4.5 mg and a ratio of 3:1:1) captured the highest number of adults on sticky traps, outperforming traps bailed with individual components or a solvent control over two weeks. Significantly, the mass trapping strategy employing these lures achieved control efficacies ranging from 62.8% to 70.7% when compared to traps without attractant, which achieved control efficacies of only 14.2% to 35.4% across three test sites in 2023. These results indicate that the combination of p-anisaldehyde, eugenol, and farnesene exhibits an additive or synergistic effect on D. minowai. In conclusion, our findings establish a theoretical framework and provide practical technological support for integrating attractant-based strategies into comprehensive thrips management strategies.